2021
DOI: 10.1097/01.ogx.0000802660.47978.73
|View full text |Cite
|
Sign up to set email alerts
|

Rates of Neuropsychiatric Disorders and Gestational Age at Birth in a Danish Population

Abstract: Gestational age (GA) is associated with brain growth and development. When the duration of gestation is not optimal, a range of adverse health outcomes in the offspring including neuropsychiatric morbidities may occur. Associations between GA and these disorders have been found in epidemiological studies that measured outcomes based on 2 or 3 levels of classification. This study aims to examine the associations between more finely defined GA groups and multiple neuropsychiatric disorders.This was a population-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 0 publications
2
9
0
Order By: Relevance
“…However, previous findings on post‐term birth and its association with the incidence of mental disabilities are not homogeneous. A few recent studies (Heinonen et al, 2016; Xia et al, 2021) have evaluated the associations between gestational age and the risk for common mental disorders in adulthood, reporting findings consistent with our results showing the decreased risk for mental disorders as gestational age increased. Our results were also supported by a recent study (Xia et al, 2021), which examined the association between gestational age groups and the incidence rates for major neuropsychiatric disorders in Denmark.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, previous findings on post‐term birth and its association with the incidence of mental disabilities are not homogeneous. A few recent studies (Heinonen et al, 2016; Xia et al, 2021) have evaluated the associations between gestational age and the risk for common mental disorders in adulthood, reporting findings consistent with our results showing the decreased risk for mental disorders as gestational age increased. Our results were also supported by a recent study (Xia et al, 2021), which examined the association between gestational age groups and the incidence rates for major neuropsychiatric disorders in Denmark.…”
Section: Discussionsupporting
confidence: 92%
“…A few recent studies (Heinonen et al, 2016; Xia et al, 2021) have evaluated the associations between gestational age and the risk for common mental disorders in adulthood, reporting findings consistent with our results showing the decreased risk for mental disorders as gestational age increased. Our results were also supported by a recent study (Xia et al, 2021), which examined the association between gestational age groups and the incidence rates for major neuropsychiatric disorders in Denmark. They found that the incidence rate of most major and subtypes of neuropsychiatric disorders in late or post‐term births (41–45 weeks) was the lowest.…”
Section: Discussionsupporting
confidence: 92%
“…Previous register‐based studies have reported inconsistent findings between preterm birth, poor foetal growth and anxiety disorders, both in children and adults 5–8,13–15 …”
Section: Discussionmentioning
confidence: 98%
“…The aetiology is complex, as it involves genetics, temperamental factors, sociodemographic factors and childhood adversities 4 . Being born preterm or with poor foetal growth, defined as being born small for gestational age (SGA), have been associated with various psychiatric disorders 5–10 11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation